2012
DOI: 10.1017/s0029665112000249
|View full text |Cite
|
Sign up to set email alerts
|

ApoE genotype: from geographic distribution to function and responsiveness to dietary factors

Abstract: ApoE is a key protein in lipid metabolism with three major isoforms. ApoE allele frequencies show non-random global distribution especially in Europe with high apoE e3 frequency in the Mediterranean area, whereas the apoE e4 genotype is enriched in Northern Europe. The apoE e4 genotype is one of the most important genetic risk factors for age-dependent chronic diseases, including CVD and Alzheimer's disease (AD). The apoE polymorphism has been shown to impact on blood lipids, biomarkers of oxidative stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 129 publications
(161 reference statements)
3
61
0
5
Order By: Relevance
“…Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013). However, environmental factors, including living conditions, diet, and living habits, were also shown to affect blood lipid levels and cerebral infarction (CI) (Egert et al, 2012;Petkeviciene et al, 2012;Rudkowska et al, 2013). Therefore, this study focused on the relationship between the ApoE gene polymorphism and dietary factors in the association with plasma lipid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013). However, environmental factors, including living conditions, diet, and living habits, were also shown to affect blood lipid levels and cerebral infarction (CI) (Egert et al, 2012;Petkeviciene et al, 2012;Rudkowska et al, 2013). Therefore, this study focused on the relationship between the ApoE gene polymorphism and dietary factors in the association with plasma lipid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that apolipoprotein E (ApoE) is a very important genetic risk factor for age-dependent chronic diseases, including CVD and AD [12]. Due to two major polymorphisms on the encoding exon 4 of this gene, three major protein isoforms, ApoE ε2, ApoE ε3 and ApoE ε4 exist [13]. It has been shown that homozygous carriers of the ApoE ε4 allele have a more than 10-fold increased risk of developing AD, possibly due to increased cholesterol levels, altered brain development early in life [12] or increased oxidative brain damage [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although these allelic forms differ from each other by only one or two amino acids at positions 112 and 158, these differences alter the APOE structure and function. There are 6 genotypes of APOE: E2/E2, E2/E3, E3/E3, E2/E4, E3/E4 and E4/E4 [11,12,13]. Their frequencies vary substantially around the world, but APOE3 is the most common almost everywhere and is often considered to be the ancestral or ‘wild-type' allele for that reason [14].…”
Section: Introductionmentioning
confidence: 99%